Optical Characteristics and Applications of AIE Racemic C6-Unsubstituted Tetrahydropyrimidines - Zhu, Qiuhua (Frontiers in Chemistry, 2021)
Racemic C6-unsubstituted tetrahydropyrimidines (THPs) are the products of an efficient five component reaction that we developed. THPs show strong AIE characteristics, that is, completely no fluorescence in different solvents but strong emission with fluorescence quantum yields (F) up to 100% upon aggregation. However, the F values of their pure enantiomers are lower than 46%. Unlike common AIE compounds with crowded aryl rotors on a -bond or on an aryl ring, THPs have three completely non-crowded aryl rotors on a non-aromatic chiral central ring (tetrahydropyrimidine). In this mini review, we firstly discuss the AIE characteristics of THPs and the influences of molecular structures on their molecular packing modes and optical properties, and then present their applications and forecast the development of other racemic AIE compounds.